INTERPRETASI STRUKTUR BAWAH PERMUKAAN MENGGUNAKAN METODE MAGNETIK (DAERAH SEKITAR SUNGAI OYO YOGYAKARTA) - Dewi Saroh Muzhaffar; Muhammad Irham Nurwidiyanto (Youngster Physics Journal, 2016)
Magnetic survey has been carried out in the area of Central Java DI Yogyakarta, arround Oyo River, aims to interpret the subsurface structure of the fault zones surrounding Patuk, Dlingo and Playen district. In this study, magnetic data acquisition was carried out in 70 points by using a PPM (Proton Precession Magnetometer) geometrics 856X models to get the values of the total magnetic field. Data Processing began with International Geomagnetic Reference Field (IGRF) to get the total magnetic anomaly. The total magnetic anomaly contour created by using Surfer that has been used to process upward continuation and then made reduction to the poles. The result of research showed the magnetic anomaly closure pair of positive and negative indicated a fault zone below the surface. The closure pair of positve and negative close to Oyo River was made an incision to determine the subsurface structure of the region by creating a model of 2-dimensional (2D) and a model of 3-dimensional (3D). In 2D modelling result show that there was a fault zone at 650 meters depth at the x coordinate 444942(UTM). It is characterised by changes on the contrast susceptibility values 0.3241 and 0.3225 on the third layers. The interpretation was reinforced by the result of 3D modelling in the area. The fault suspected to be around arround Oyo River, Gunung Kidul with north-south direction.